Evaluation of triglyceride: HDL-C ratio and Non-HDL-C as harbingers of increased cardiovascular risk in metabolic syndrome - R., Dharuni; B. V., Maruthi Prasad; H. L., Vishwanath; R., Harish (International Journal of Research in Medical Sciences, 2016)
Background: Metabolic syndrome is an aggregate of conditions that together increases the risk of developing cardiovascular disease and type 2 diabetes mellitus. Dyslipidemia consisting of elevated triglyceride, decreased HDL, and altered triglyceride to high density lipoprotein- Cholesterol (TG/HDL-C) ratio is useful in predicting cardiometabolic risk and insulin resistance. The present study aimed to compile further evidence for clinical utility of TG/HDL-C ratio and Non HDL-C as simple, cost effective tools for early identification of cardiovascular disease risk in metabolic syndrome. Methods: This study was carried out with hundred subjects. Fifty of these subjects were diagnosed with metabolic syndrome according to National Cholesterol Education Program Adult Treatment Panel III; while other fifty were age and gender matched healthy control subjects. Results: The impact of cardiometabolic markers on metabolic syndrome was assessed separately in men and women by applying Mann Whitney ‘U’ test. Study showed highly significant increase in TG, HDL, TC/TG and TG/HDL-C ratio in women compared to men with p<0.01. The odds ratio of TG/HDL for women showed the highest ratio of 6, 95% CI (1.5225 to 23.6401) p=0.006 compared to men 4.9583, 95% CI (1.0088-24.3711), p=0.004. Conclusions: This study demonstrated that TG/HDL-C ratio and Non HDL-C are strongly associated with metabolic syndrome in urban population. In comparison, TG/HDL-C is a better predictor of metabolic syndrome than non-HDL-C.